A Web-based Game for Teaching Facial Expressions to Schizophrenic Patients - Gülkesen, Kemal Hakan; Işleyen, Filiz; Cinemre, Buket; Samur, Mehmet Kemal; Kaya, Semiha Şen; Zayim, Neşe (Applied Clinical Informatics, 2017)
Background: Recognizing facial expressions is an important social skill. In some psychological disorders such as schizophrenia, loss of this skill may complicate the patient’s daily life. Prior research has shown that information technology may help to develop facial expression recognition skills through educational software and games.Objectives: To examine if a computer game designed for teaching facial expressions would improve facial expression recognition skills of patients with schizophrenia.Methods: We developed a website composed of eight serious games. Thirty-two patients were given a pre-test composed of 21 facial expression photographs. Eighteen patients were in the study group while 14 were in the control group. Patients in the study group were asked to play the games on the website. After a period of one month, we performed a post-test for all patients.Results: The median score of the correct answers was 17.5 in the control group whereas it was 16.5 in the study group (of 21) in pretest. The median post-test score was 18 in the control group (p=0.052) whereas it was 20 in the study group (p<0.001).Conclusions: Computer games may be used for the purpose of educating people who have difficulty in recognizing facial expressions.Citation: Gülkesen KH, Işleyen F, Cinemre B, Şamur MK, Sen Kaya S, Zayim N. A web-based game for teaching facial expressions to schizophrenic patients. Appl Clin Inform 2017; 8: 719–730 https://doi.org/10.4338/ACI-2016-10-RA-0172
Keywords: Facial expression; video games; schizophrenia